Orthognathic surgery improves quality of life: a survey clinical study - Esengul Sen; Hatice Duran; Merve Sarı; Nihat Akbulut; Osman Demir (BMC, 2024)
Abstract Background The aim of this study was to evaluate the quality of life (QoL) of patients with dentofacial deformity (n = 107) compared with that of healthy individuals (n = 108) from 2019 to 2020. Methods Oral Health Impact Profile 14 (OHIP-14) and the Orthognathic Quality of Life Questionnaire (OQLQ) were administered to the individuals before surgery (T1) and 6 months after surgery (T2). Results Preoperative scores (T1) were greater in the surgical group than in the control group in all domains of both surveys (p ≤ 0.001). Postoperative scores (T2) in the surgery group decreased significantly after surgery in all domains in both surveys (p < 0.001). The OHIP-14 scores in the control group at T2 were significantly greater than those in the other domains except for functional limitation at T1. The type of surgery had no effect on quality of life. Class III patients had higher preoperative scores in certain domains. Postoperative physical disability (p = 0.037), physical pain (p = 0.047), and preoperative social disability (p = 0.030) scores of OHIP-14 awareness of dentofacial aesthetics of OQLQ (p = 0.019) were found to be higher in females than in males. Conclusions The results showed that orthognathic surgery positively affected quality of life. The control group showed differences in T1 and T2 scores, which can be attributed to their psychological status.